2019
DOI: 10.3892/ol.2019.11043
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of regorafenib in acute pulmonary carcinomatous lymphangitis as a manifestation of rectal cancer: A case report

Abstract: Recent therapeutic advancements have prolonged the survival duration of patients with metastatic or recurrent colorectal cancer even during salvage treatment. Although treatment with regorafenib and trifluridine/tipiracil combination has exhibited apparent survival benefits, clear and objective evidence of a response to these drugs is scarce. Herein, the present study reports the case of a patient with rectal cancer refractory to multiple surgical interventions and standard chemotherapy. Treatment with regoraf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…The reported median survival time of patients with pulmonary carcinomatous lymphangitis was 3 months, 23 and our study also confirmed similar prognostic outcomes. Effective chemotherapy was reported for carcinomatous lymphangitis, 24,25 but prompt chemotherapy was considered to be indemonstrable in patients with skeletal metastasis if the primary malignancy is not known. In this study, treatment for patients with respiratory failure was consequently only palliative treatment, which might not have improved their prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…The reported median survival time of patients with pulmonary carcinomatous lymphangitis was 3 months, 23 and our study also confirmed similar prognostic outcomes. Effective chemotherapy was reported for carcinomatous lymphangitis, 24,25 but prompt chemotherapy was considered to be indemonstrable in patients with skeletal metastasis if the primary malignancy is not known. In this study, treatment for patients with respiratory failure was consequently only palliative treatment, which might not have improved their prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…Researchers have reported few evaluations of the efficacy and safety of regimens for PLC due to its relatively low prevalence and dispersed locations of primary tumors. Isolated studies included the assessment of the remission of PLC and disease control with hormonal therapy ( 4 ), chemotherapy ( 5 ) ( 6 ), antiangiogenic drugs, including apatinib ( 7 ), regorafenib ( 8 ), bevacizumab ( 9 ), cetuximab ( 10 ), and gefitinib ( 11 , 12 ), and immunotherapy ( 13 ). These highlighted potential treatment strategies for patients who develop PLC and studies with detailed descriptions are warranted to guide the management of patients.…”
Section: Introductionmentioning
confidence: 99%